Pendidikan Ilmu Kalam dalam Pandangan Ismail Alfaruqi dan Hasan Hanafi - Nurdiani Nurdiani (Program Pascasarjana UIN Sumatera Utara, 2022)
Kalam education should be based on the principles of justice and truth that are the foundation of Islamic teachings. In addition, kalam education should help one to understand social and political problems critically and develop appropriate solutions to overcome them. Hanafi and Al Faruqi are helping someone to understand the teachings of Islam comprehensively, strengthening faith and belief in religious teachings, and helping someone to understand and overcome social and political problems in a way that is in accordance with the principles of justice and truth which are the basis of Islamic teachings. This research uses Library Research, which is a research method that uses written sources such as books, journals, documents, or notes related to Kalam Science Education in the Views of Ismail Alfaruqi and Hasan Hanafi.